CRISPR-mediated mutations in the ABC transporter gene ABCA2 confer pink bollworm resistance to Bt toxin Cry2Ab - Jeffrey A. Fabrick (Nature Portfolio, 2021)
Abstract Crops genetically engineered to produce insecticidal proteins from Bacillus thuringiensis (Bt) have many benefits and are important globally for managing insect pests. However, the evolution of pest resistance to Bt crops reduces their benefits. Understanding the genetic basis of such resistance is needed to better monitor, manage, and counter pest resistance to Bt crops. Previous work shows that resistance to Bt toxin Cry2Ab is associated with mutations in the gene encoding the ATP-binding cassette protein ABCA2 in lab- and field-selected populations of the pink bollworm (Pectinophora gossypiella), one of the world’s most destructive pests of cotton. Here we used CRISPR/Cas9 gene editing to test the hypothesis that mutations in the pink bollworm gene encoding ABCA2 (PgABCA2) can cause resistance to Cry2Ab. Consistent with this hypothesis, introduction of disruptive mutations in PgABCA2 in a susceptible strain of pink bollworm increased the frequency of resistance to Cry2Ab and facilitated creation of a Cry2Ab-resistant strain. All Cry2Ab-resistant individuals tested in this study had disruptive mutations in PgABCA2. Overall, we found 17 different disruptive mutations in PgABCA2 gDNA and 26 in PgABCA2 cDNA, including novel mutations corresponding precisely to single-guide (sgRNA) sites used for CRISPR/Cas9. Together with previous results, these findings provide the first case of practical resistance to Cry2Ab where evidence identifies a specific gene in which disruptive mutations can cause resistance and are associated with resistance in field-selected populations.